Recent Advances in Molecular Tools and Pre-Breeding Activities in White Lupin (Lupinus albus) - Andrea Tosoroni; Valerio Di Vittori; Laura Nanni; Evan Musari; Simone Papalini; Elena Bitocchi; Elisa Bellucci; Alice Pieri; Sofia Ghitarrini; Karolina Susek; Roberto Papa (Plants)
The higher adaptation of landraces to local agroclimatic conditions resulting from natural and moderate artificial selection by farmers within specific environments makes them a crucial source of alleles and genotypes for cultivation and breeding programs. Unlike modern cultivars, which have been developed under more intense artificial selective pressures, landraces exhibit a broader genetic base that has been documented in landrace collections for many crops. This review provides an overview of the importance of genetic resource valorisation in legume species, focusing on cultivated species of the Lupinus genus, particularly white lupin (Lupinus albus). On the one hand, legumes, including Lupins, are considered a crucial alternative source of protein within the framework of more sustainable agriculture. On the other hand, they are often neglected species in terms of breeding efforts, despite receiving increasing attention in recent years. Here, we also report on the latest advances in the development of genomic tools, such as the novel pangenome of white lupin and the identification of markers and loci for target adaptation traits, such as tolerance to alkaline soils, which can effectively support the breeding of Lupinus albus, especially for the introgression of desirable alleles from locally adapted varieties.